The Interaction of the Soybean Seed High Oleic Acid Oil Trait With Other Fatty Acid Modifications. (11th February 2018) - Bilyeu, Kristin; Škrabišová, Mária; Allen, Doug; Rajcan, Istvan; Palmquist, Debra E.; Gillen, Anne; Mian, Rouf; Jo, Hyun
Abstract: Oil value is determined by the functional qualities imparted from the fatty acid profile. Soybean oil historically had excellent use in foods and industry; the need to increase the stability of the oil without negative health consequences has led to a decline in soybean oil use. One solution to make the oil stable is to have high oleic acid (>70%) and lower linolenic acid content in the oil. Other fatty acid profile changes are intended to target market needs: low‐saturated fatty acid and high stearic acid content in the oil. The objective of this study is to determine the interaction of the high oleic acid oil trait with other alleles controlling fatty acid profiles. Soybean lines containing high oleic acid allele combinations plus other fatty acid modifying alleles were produced, and the seed was produced in multiple field environments over 2 years. Stable high oleic acid with low linolenic acid (<3.0%) was achieved with a 4‐allele combination. The target of >20% stearic acid in the seed oil was not achieved. Reducing total saturated fatty acids below 7% in a high oleic acid background was possible with mutant alleles of both an acyl‐ACP thioesterase B and a β‐ketoacyl‐[acyl‐carrier‐protein] synthase III gene. The results identified allele combinations that met the target fatty acid profile thresholds and were most stable across environments.